Genomic Characterization of a Mercury Resistant Arthrobacter sp. H-02-3 Reveals the Presence of Heavy Metal and Antibiotic Resistance Determinants - Pathak, Ashish; Jaswal, Rajneesh; Chauhan, Ashvini (Frontiers in Microbiology, 2020)
Nuclear production and industrial activities led to widespread contamination of the Department of Energy managed Savannah River Site (SRS), located in South Carolina, USA. The H-02 wetland system was constructed in 2007 for the treatment of industrial and storm water runoff from the SRS Tritium Facility. Albeit at low levels, mercury (Hg) has been detected in the soils of the H-02 wetland ecosystem. In anoxic sediments, Hg is typically methylated by anaerobic microbiota, forming the highly neurotoxic methylmercury (MeHg), which biomagnifies across food webs. However, in surficial oxic wetland soils, microbially-mediated demethylation and/or volatilization processes can transform Hg2+ into the less toxic Hg0 form which is released into the atmosphere, thus circumventing MeHg formation. To obtain a deeper understanding on bacterial Hg volatilization, a robust Hg-resistant (HgR) bacteria, called as strain H-02-3 was isolated from the H-02 soils. A draft genome sequence of this strain was obtained at a coverage of 700x, which assembled in 44 contigs with an N50 of 171,569 bp. The genomic size of the strain H-02-3 was 4,708,612 bp with a total number of 4,240 genes; phylogenomic analysis revealed the strain as an Arthrobacter species. Comparative genomics revealed the presence of 1100 unique genes in strain H-02-3, representing 26.7% of the total genome; many identified previously as metal resistance genes (MRGs). Specific to Hg-cycling, the presence of mercuric ion reductase (merA), the organomercurial lyase (merB), and the mercuric resistance operon regulatory protein, were identified. By inference, it can be proposed that the organomercurial lyase facilitates the demethylation of methylmercury into Hg2+ which is then reduced to Hg0 by MerA in strain H-02-3. Furthermore, gene prediction using resistome analysis of strain H-02-3 revealed the presence of several antibiotic resistance genes (ARGs), that statistically correlated with the presence of metal resistant genes (MRGs), suggesting co-occurrence patterns of MRGs and ARGs in the strain. Overall, this study delineates environmentally beneficial traits that likely facilitates survival of Arthrobacter sp. H-02-3 within the H-02 wetland soil. Finally, this study also highlights the largely ignored public health risk associated with the co-development of ARGs and MRGs in bacteria native to historically-contaminated soils.